Our God and the God of Our Parents: Faith and Identity - Matei, Carina (Journal for the study of religions and ideologies, 2023)
One of the main developmental tasks of emerging adulthood is finding the answer to the question "Who am I"? This quest can be guided directly and indirectly by parents, culture, faith, and social context. Finding the answer before starting adulthood can contribute to the individuals’ well-being later on in life. By using inductive thematic analysis, we aim to explore and capture the personal view of religious faith in a sample of Orthodox Christian religious emerging adults from Romania. The in-depth interviews allowed for a theme relating to identity and religious teachings from parents to emerge in an organic manner. Following the protocol for our inductive analysis, we reviewed the research literature on these topics. We begin by presenting the review of the literature on the main concepts that relate to our data. We continue by presenting the data from a small segment of an extended qualitative research. Finally, we discuss the implications on a theoretical level both from a psychological and theological perspective, and also on a practical one by referring to psychological and theological aid.